Benin : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
This 2004 Article IV Consultation highlights that Benin's economic performance over 2001-03 was strong. Real GDP growth averaged 5.3 percent, driven by growth in the cotton and services sectors. Inflation was low, averaging 2.6 percent per year. The external current deficit narrowed in 2003 as terms of trade improved. Progress in the structural area was mixed. However, macroeconomic performance since the beginning of 2004 has suffered from a poor cotton crop and the tightening of import restrictions by Nigeria.